The role of variability and risk on the persistence of shared-enemy, predator-prey assemblages. - Bonsall, M (2003)
The role of indirect effects such as apparent competition in structuring predator-prey assemblages has recently received empirical attention. That one prey species can be excluded by the impact of a shared-enemy contrasts with the known diversity of multispecies predator-prey interactions. Here, the role of predator foraging among patches of two different prey species is examined as a mechanism that can mediate coexistence in multispecies prey-predator assemblages. Specifically, models of host-parasitoid interactions are constructed to analyse how different types of aggregative behaviour (generated by host-dependent and host-independent responses) affect persistence of the assemblage. How the distribution of hosts and the response of the parasitoid to these distributions can influence coexistence is shown. A generic explanation for coexistence suggests that it is the variability rather than the precise functional relationship that is critical for coexistence under shared-enemy interactions.